PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA SUKOLILO MELALUI PEMANFAATAN LIMBAH KERTAS MENJADI PRODUK BERNILAI EKONOMI - ANDARI, TRI; LUSIANA, RESTU (Jurnal Terapan Abdimas, 2017)
AbstractThe purpose of this training is the training participants can process the waste of paper and then process it into recycled paper ready for sale to the basic ingredients of craft and production of handicrafts made from recycled paper, master the skills and attitudes include the training of administrative, entrepreneurial management, organization, and marketing. The training activities carried out in the village Sukolilo Jiwan subdistrict, Madiun Regency. This activity uses two methods of approach, the first separation of training activities and the processing of waste paper and paper-based creative production. And the second is training and mentoring organization, management and entrepreneurship. Assistance activities primarily intended to increase the value of selling their production of processed waste so it can be accepted with a high value in the market. Training is done in six stages, namely the preparatory stage, the introduction stage, the stage of establishment of the system, stages of creative production, sales stage, and the stage of development. The results of the activities are 1) most of the trainees can follow every stage of the training given to the good, but there are some stages that have not been implemented, namely the development phase in view of the time constraints, 2) Kesejahateraan villagers Sukolilo increased through the utilization of waste paper into recycled paper which is then processed into a product of creative economic value. AbstrakTujuan dari kegiatan pelatihan ini adalah peserta pelatihan dapat mengolah sampah kertas kemudian memprosesnya menjadi kertas daur ulang siap jual untuk bahan dasar kerajinan dan produksi hasil kerajinan berbahan dasar kertas daur ulang, menguasai keterampilan dan sikap meliputi pelatihan administrasi, manajemen kewirausahaan, organisasi, dan pemasaran. Kegiatan pelatihan dilakukan di Desa Sukolilo Kecamatan Jiwan Kabupaten Madiun. Kegiatan ini menggunakan dua metode pendekatan, yang pertama kegiatan pelatihan pemisahan serta pengolahan limbah kertas dan produksi kreatif berbahan dasar kertas. Dan yang kedua adalah pelatihan dan bimbingan organisasi, manajemen dan kewirausahaan. Kegiatan Pendampingan terutama ditujukan untuk meningkatkan nilai hasil jual produksi olahan sampah sehingga bisa diterima dengan nilai tinggi di pasar. Pelatihan dilakukan dalam enam tahapan yaitu tahap persiapan, tahap pengenalan, tahap pembentukan sistem, tahap produksi kreatif, tahap penjualan, dan tahap pengembangan. Adapun hasil pelaksanaan kegiatan adalah 1) sebagian besar peserta pelatihan dapat mengikuti setiap tahapan pelatihan yang diberikan dengan baik, namun ada beberapa tahap yang belum terlaksana yaitu tahap pengembangan mengingat keterbatasan waktu, 2) Kesejahateraan masyarakat desa Sukolilo meningkat melalui pemanfaatan limbah kertas menjadi kertas daur ulang yang kemudian diolah menjadi produk kreatif yang bernilai ekonomi.